2023
DOI: 10.4168/aair.2023.15.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Disorders and Their Risks of Migraine: A Nationwide Population-Based Cohort Study

Abstract: Purpose Migraine is a relatively common neurologic disorder. A possible link between atopic disorders and migraine has been suggested. This study investigated atopic disorders and their risks of migraine in the Korean population. Methods From the Korean National Health Insurance Service database, patients aged ≥ 20 years who underwent health screening between January and December of 2009 were enrolled. To evaluate the risk of migraine, Cox proportional hazards regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Consistent with the previous study, AD is positively associated with migraine in the population-based cohort study and adults with AD were 89% more likely to have a diagnosis of migraine. 1,5 Our novel findings further enhance our understanding of these associations and suggest causal links attributable to genetic factors; however, the potential sources of bias or confounding related to MR should be also considered. We discovered an increased risk of migraine among patients with AD.…”
Section: E T T E R T O T H E E D I T O R a Two-sample Bidirectional M...mentioning
confidence: 64%
“…Consistent with the previous study, AD is positively associated with migraine in the population-based cohort study and adults with AD were 89% more likely to have a diagnosis of migraine. 1,5 Our novel findings further enhance our understanding of these associations and suggest causal links attributable to genetic factors; however, the potential sources of bias or confounding related to MR should be also considered. We discovered an increased risk of migraine among patients with AD.…”
Section: E T T E R T O T H E E D I T O R a Two-sample Bidirectional M...mentioning
confidence: 64%
“…As shown in Table 1, most studies reported that allergic/atopic disorders (including allergic rhinitis and atopic dermatitis), asthma, and migraine are reciprocally significantly associated [17][18][19][20][21][22][23][24][25][26][27]. The overlap between allergic disorders without asthma [37][38][39] and atopic dermatitis/eczema [40][41][42][43] with migraine is also consolidated.…”
mentioning
confidence: 99%